Four new dammarane-type triterpenes derivatives from hydrolyzate of total Gynostemma pentaphyllum saponins and their bioactivities. Issue 11 (3rd June 2019) - Zhang, Xiaoshu; Shi, Guohui; Liu, Mingbing; Chen, Rong; Wu, Xiaojun; Zhao, Yuqing
Abstract: Phytochemical investigation of hydrolysate of total G. pentaphyllum saponins led to the isolation of four novel triterpenes, Gypensapogenin U (1 ), Gypensapogenin V (2 ), Gypensapogenin W (3 ) and Gypensapogenin X (4 ). The structures of these compounds were identified by 1D, 2D-NMR and HR-ESI-MS evidences. Additionally, the protective activity of these new compounds against cardiomyocytes injury induced by H2 O2 and their cytotoxic activity against t-HSC/Cl-6 cells were evaluated. Abstract :